Adiposity and risk of ischaemic and haemorrhagic stroke in 0·5 million Chinese men and women: a prospective cohort study. Issue 6 (June 2018) - Chen, Zhengming; Iona, Andri; Parish, Sarah; Chen, Yiping; Guo, Yu; Bragg, Fiona; Yang, Ling; Bian, Zheng; Holmes, Michael V; Lewington, Sarah; Lacey, Ben; Gao, Ruqin; et al.
Summary: Background: China has high stroke rates despite the population being relatively lean. Uncertainty persists about the relevance of adiposity to risk of stroke types. We aimed to assess the associations of adiposity with incidence of stroke types and effect mediation by blood pressure in Chinese men and women. Methods: The China Kadoorie Biobank enrolled 512 891 adults aged 30–79 years from ten areas (five urban and five rural) during 2004–08. During a median 9 years (IQR 8–10) of follow-up, 32 448 strokes (about 90% confirmed by neuroimaging) were recorded among 489 301 participants without previous cardiovascular disease. Cox regression analysis was used to produce adjusted hazard ratios (HRs) for ischaemic stroke (n=25 210) and intracerebral haemorrhage (n=5380) associated with adiposity. Findings: Mean baseline body-mass index (BMI) was 23·6 kg/m 2 (SD 3·2), and 331 723 (67·8%) participants had a BMI of less than 25 kg/m 2 . Throughout the range examined (mean 17·1 kg/m 2 [SD 0·9] to 31·7 kg/m 2 [2·0]), each 5 kg/m 2 higher BMI was associated with 8·3 mm Hg (SE 0·04) higher systolic blood pressure. BMI was positively associated with ischaemic stroke, with an HR of 1·30 (95% CI 1·28–1·33 per 5 kg/m 2 higher BMI), which was generally consistent with that predicted by equivalent differences in systolic blood pressure (1·25 [1·24–1·26]). The HR for intracerebral haemorrhage (1·11 [1·07–1·16] per 5 kg/m 2 higher BMI) was less extreme, and much weaker than that predicted by the corresponding difference in systolic blood pressure (1·48 [1·46–1·50]). Other adiposity measures showed similar associations with stroke types. After adjustment for usual systolic blood pressure, the positive associations with ischaemic stroke were attenuated (1·05 [1·03–1·07] per 5 kg/m 2 higher BMI); for intracerebral haemorrhage, they were reversed (0·73 [0·70–0·77]). High adiposity (BMI >23 kg/m 2 ) accounted for 14·7% of total stroke (16·5% of ischaemic stroke and 6·7% of intracerebral haemorrhage). Interpretation: In Chinese adults, adiposity was strongly positively associated with ischaemic stroke, chiefly through its effect on blood pressure. For intracerebral haemorrhage, leanness, either per se or through some other factor (or factors), might increase risk, offsetting the protective effects of lower blood pressure. Funding: UK Wellcome Trust, UK Medical Research Council, British Heart Foundation, Cancer Research UK, Kadoorie Charitable Foundation, Chinese Ministry of Science and Technology, Chinese National Natural Science Foundation.